Society of Vacuum Coaters : 48th Annual Technical Conference proceedings, April 23-28, 2005, Denver, Colorado. (Society of Vacuum Coaters, 2005)
The Society of Vacuum Coaters is a non-profit professional and educational organization, dedicated to the development of equipment and processes for high-volume production of coatings using vacuum-based processes.
Keywords: Vapor-plating -- Congresses.; elektronické knihy; electronic books